Agonistic Anti-CD40 Antibody Triggers an Acute Liver Crisis With Systemic Inflammation in Humanized Sickle Cell Disease Mice - Yalamanoglu, Ayla; Dubach, Irina L.; Schulthess, Nadja; Ingoglia, Giada; Swindle, Delaney C.; Humar, Rok; Schaer, Dominik J.; Buehler, Paul W.; Irwin, David C.; Vallelian, Florence (Frontiers in Immunology, 2021)
Sickle cell disease (SCD) is an inherited hemolytic disorder, defined by a point mutation in the β-globin gene. Stress conditions such as infection, inflammation, dehydration, and hypoxia trigger erythrocyte sickling. Sickled red blood cells (RBCs) hemolyze more rapidly, show impaired deformability, and increased adhesive properties to the endothelium. In a proinflammatory, pro-coagulative environment with preexisting endothelial dysfunction, sickled RBCs promote vascular occlusion. Hepatobiliary involvement related to the sickling process, such as an acute sickle hepatic crisis, is observed in about 10% of acute sickle cell crisis incidents. In mice, ligation of CD40 with an agonistic antibody leads to a macrophage activation in the liver, triggering a sequence of systemic inflammation, endothelial cell activation, thromboses, and focal ischemia. We found that anti-CD40 antibody injection in sickle cell mice induces a systemic inflammatory and hemodynamic response with accelerated hemolysis, extensive vaso-occlusion, and large ischemic infarctions in the liver mimicking an acute hepatic crisis. Administration of the tumor necrosis factor-α (TNF-α) blocker, etanercept, and the heme scavenger protein, hemopexin attenuated end-organ damage. These data collectively suggest that anti-CD40 administration offers a novel acute liver crisis model in humanized sickle mice, allowing for evaluation of therapeutic proof-of-concept.